Developing solutions roadmaps for rice production in flooding area of the Vietnamese Mekong Delta adapting to uncertain changes in climate and surface water resources - Hoang, Hong Minh; Nguyen Hong Tin,; Dinh Diep Anh Tuan,; Van Pham Dang Tri, (Vietnam Journal of Science and Technology, 2023)
Climate change, hydro-power dams and socio-economic development in the upper Mekong River, have caused changes in surface water resources and agricultural transformation in the Vietnamese Mekong Delta (VMD). It is unpredictable and influences decision-making processes on water resource management. This study aims at applying the DAPP (Dynamic Adaptive Policy Pathways) approach to develop solution roadmaps supporting rice production in the Mekong Delta projection to 2030 under the context of uncertain changes on surface water resources. Data were collected from local officers, farmers, experts at Can Tho University, Technical University Delft, and Utrecht University using semi-structured interview techniques including workshops, group discussions, and in-depth interviews. The consolidated solutions from stakeholder’s opinions were evaluated at different socio-economic and environmental dimensions, specially focused on the time of tipping point of each solution. The study results show that two solution roadmaps were developed as sample scenarios to promote rice production in the upper area of the VMD. The determination of the solutions roadmaps based on the agreement of the stakeholders, which is a new feature of this approach in linking many stakeholders for the general development of the region. The DAPP approach could be suitable to support decision-making on surface water resources management in the context of uncertain changes. Therefore, further studies can apply this approach to other regions in the VMD which will support to reinforce and demonstrate the applicability of the DAPP approach on supporting decision-making in the face of increasingly uncertain changes in the VMD.